2006
DOI: 10.1097/01.ijg.0000212207.79899.85
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Suprachoroidal Drainage for the Surgical Treatment of Intractable Glaucoma

Abstract: This novel surgical approach and the placement of the silicone tube described here have several advantages. Its intrascleral course minimizes the risk of conjunctival erosion and associated infections. No cyclodialysis is performed. Connection to the suprachoroidal space exploits the resorptive capability of the choroid. It guarantees drainage but also provides a natural counterpressure, avoiding severe postoperative hypotony. The suprachoroidal shunt presented here achieves good follow-up results in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 22 publications
2
39
1
4
Order By: Relevance
“…In a rabbit model of the suprachoroidal shunt [15], massive formation of scar tissue was observed as early as 2 weeks after surgery, with the histologic examination revealing fibrosis with similarities to proliferative vitreoretinopathy specimens. The authors suggested that scar tissue derives from fibroblasts transformed from retinal pigment epithelial cells of suprachoroid, as a consequence of the surgical trauma.…”
Section: Discussionmentioning
confidence: 95%
“…In a rabbit model of the suprachoroidal shunt [15], massive formation of scar tissue was observed as early as 2 weeks after surgery, with the histologic examination revealing fibrosis with similarities to proliferative vitreoretinopathy specimens. The authors suggested that scar tissue derives from fibroblasts transformed from retinal pigment epithelial cells of suprachoroid, as a consequence of the surgical trauma.…”
Section: Discussionmentioning
confidence: 95%
“…As described by Jordan et al [5], we first made a fornixbased conjunctival flap, then prepared 4 9 4-mm superficial and 3 9 3-mm deep posterior limbus-based scleral flaps (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…The virtual space between the external surface of the choroid and the internal surface of the sclera does not clinically manifest under physiological conditions. However, this suprachoroidal space is reported to be used to achieve glaucoma shunting in eyes with cicatrized conjunctiva [1,5].…”
Section: Introductionmentioning
confidence: 98%
“…Another approach using a tube implant for suprachoroidal drainage has been described by Jordan and coworkers [41]. Using a standard trabeculectomy approach, a silicone tube was inserted to connect the anterior chamber with the suprachoroidal space via an intrascleral route, to avoid conjunctival erosion or infection.…”
Section: Implants To Increase Uveoscleral Outflowmentioning
confidence: 99%